Health Behavior Decision-making in African-American Adults Diagnosed with Schizophrenia. (3rd July 2015) - Findlay, Lillian J.; El-Mallakh, Peggy; Howard, Patricia B.; Hatcher, Jennifer; Clark, James J.
Abstract : Little is known about the factors that influence health behavior decision-making among people with schizophrenia. The purpose of this qualitative study was to describe the processes used by 10 African-American adults with schizophrenia when making health behavior decisions and identification of perceived barriers and facilitators to health. Three phases of health behavior decision-making were identified: Recognizing Complex Components of Health, Personalizing Components of Health, and Tracking Health Status. Findings may guide clinicians' efforts to improve the health status of patients, as well as influence future research in understanding health behavior decision-making among vulnerable populations.